The effects of vitamin D supplementation on metabolic profiles and gene expression of insulin and lipid metabolism in infertile polycystic ovary syndrome candidates for in vitro fertilization - Majid Dastorani; Esmat Aghadavod; Naghmeh Mirhosseini; Fatemeh Foroozanfard; Shahrzad Zadeh Modarres; Mehrnush Amiri Siavashani; Zatollah Asemi (BMC, 2018)
Abstract Background Vitamin D deficiency in women diagnosed with polycystic ovary syndrome (PCOS) remarkably decreases the chance of pregnancy, which might be related to its impact on metabolic abnormalities in these patients. It is hypothesized that vitamin D supplementation influences metabolic profile of these patients and indirectly might affect fertility and the outcomes. Therefore, this study was conducted to determine the effects of vitamin D supplementation on the levels of anti-Müllerian hormone (AMH), metabolic profiles, and gene expression of insulin and lipid metabolism in infertile women with PCOS who were candidate for in vitro fertilization (IVF). Methods This study was a randomized, double-blinded, placebo-controlled trial conducted among 40 infertile women, aged 18-40 years, diagnosed with PCOS and was candidate for IVF. Participants were randomly assigned into two intervention groups for receiving either 50,000 IU vitamin D or placebo (n = 20 each group) every other week for 8 weeks. Gene expression for insulin and lipid metabolism was conducted using peripheral blood mononuclear cells (PBMCs) of women with PCOS, via RT-PCR method. Results Vitamin D supplementation led to a significant reduction in serum AMH (− 0.7 ± 1.2 vs. − 0.1 ± 0.5 ng/mL, P = 0.02), insulin levels (− 1.4 ± 1.6 vs. -0.3 ± 0.9 μIU/mL, P = 0.007), homeostatic model of assessment for insulin resistance (− 0.3 ± 0.3 vs. -0.1 ± 0.2, P = 0.008), and a significant increase in quantitative insulin sensitivity check index (+ 0.009 ± 0.01 vs. + 0.001 ± 0.004, P = 0.04), compared with the placebo. Moreover, following vitamin D supplementation there was a significant decrease in serum total- (− 5.1 ± 12.6 vs. + 2.9 ± 10.9 mg/dL, P = 0.03) and LDL-cholesterol levels (− 4.5 ± 10.3 vs. + 2.5 ± 10.6 mg/dL, P = 0.04) compared with the placebo. Conclusion Overall, the findings of this trial supported that 50,000 IU vitamin D supplementation every other week for 8 weeks had beneficial effects on insulin metabolism, and lipid profile of infertile women with PCOS who are candidate for IVF. These benefits might not be evident upon having sufficient vitamin D levels. Trial registration This study was retrospectively registered in the Iranian website (www.irct.ir) for clinical trials registration (http://www.irct.ir: IRCT20170513033941N27).